Sustainability in finance: banking on the planet - Jeucken, Marcel (Sheffield, 2004)
"Financial institutions are often the crucial factor in a society's progress toward sustainable development. Yet financial workers and public policy researchers are largely unaware of this role. Sustainability in Finance seeks to bridge this gap as it posits a theoretical foundation for a finance-policy partnership. The volume presents an innovative analysis of current practices at both global financial institutions and banks in developing countries and ultimately offers a valuable consideration of the future of sustainable development."